Transportation Algorithm for Optimizing Renewable Energy Resources Utilization at Rural Areas - Woldeyohannes, A.; Woldemichael, D.; Eng, Z.; Lim, Chye Ing (Trans Tech Publications, 2015)
his paper aims to address the issues related to renewable energy (RE) resources optimization at rural areas. A transportation algorithm is proposed in order to optimize the utilization of renewable energy and allocate various renewable energy resources to different demand stations. A rural area in Sarawak, Malaysia is selected as a pilot area for implementing the proposed method. The total annual energy demand for the pilot research area is 860,567.12 kWh, while the annual renewable energy potentially available is 879,419.48 kWh. The simulation results of this transportation model reflect that although there is a potential for solar and wind energy at the selected rural area, the model has selected hydropower and biomass as a more viable option. The results obtained from the proposed transportation model have been verified with the results of other RE studies. It is proven that the developed model could be used as a decision making tool to evaluate application of various alternative renewable energy resources and to determine the optimal location for development of these resources.